2008
DOI: 10.1016/j.visres.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Differential aging of motion processing mechanisms: Evidence against general perceptual decline

Abstract: While the percentage of older people in our society is steadily increasing, knowledge about perceptual changes during healthy aging is still limited. We investigated age effects on visual motion perception in order to differentiate between general decline and specific vulnerabilities. A total of 119 subjects ranging in age from 20 to 82 years participated in our study. Perceptual thresholds for different types of motion information, including translational motion, expanding radial flow, and biological motion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
156
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(189 citation statements)
references
References 78 publications
28
156
5
Order By: Relevance
“…In agreement with previous studies, they found an age-related deterioration in global motion processing. Billino, Bremmer and Gegenfurtner (2008) also found a deleterious effect of age on translational global motion perception in participants ranging from 20 to 82 years. However, the precise extent of age-related deficits are unresolved with estimates of deterioration between participants in their 20s and 70s ranging from around 2 to 13.5 %.…”
Section: Global Motionmentioning
confidence: 73%
See 4 more Smart Citations
“…In agreement with previous studies, they found an age-related deterioration in global motion processing. Billino, Bremmer and Gegenfurtner (2008) also found a deleterious effect of age on translational global motion perception in participants ranging from 20 to 82 years. However, the precise extent of age-related deficits are unresolved with estimates of deterioration between participants in their 20s and 70s ranging from around 2 to 13.5 %.…”
Section: Global Motionmentioning
confidence: 73%
“…The results of other studies suggest that, whilst older women do have significantly higher coherence thresholds (i.e. worse performance), this is also true of younger female participants (Billino et al, 2008), and perhaps is indicative of a general gender difference in global motion perception, rather than one specific to age. Snowden and Kavanagh (2006) also found gender effects on both tasks of motion coherence and speed discrimination, but none of these interacted with age.…”
Section: The Influence Of Gendermentioning
confidence: 87%
See 3 more Smart Citations